Perceived Rewards of Nursing Among Christian Nursing Students in Bangalore, India - Garner, Shelby L. (Journal of religion and health, 2015)
Nurses in India face significant challenges and often migrate to practice nursing abroad. Few studies have focused on the rewards of nursing in India. The aim of this study was to illuminate perceived rewards of nursing among Christian student nurses in Bangalore, India. Photovoice, a participatory action methodology was used, and 14 Christian student nurses participated in the study. Thematic interpretation of photographs, journals, critical group dialog sessions, and observational field notes resulted in the identification of two main themes. These themes included intrinsic rewards and lifelong benefits of nursing in India.